Comparative study on the teacher-librarian collaboration program of level II PAASCU accredited schools in Quezon City - Castillo, Neowy Lindsay G.; Silverio, Rochelle S. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2014)
Teachers and librarians are instructional partners. They both have corresponding roles which are integral to a school's success. In theory, teacher librarian collaboration has a positive impact not only to the students, but to the teachers and librarians as well. With the librarian and teachers jointly planning and monitoring instruction, the needs of the students will be more effectively met. Teachers and librarians are instructional partners. They both have corresponding roles which are integral to a school's success. In theory, teacher librarian collaboration has a positive impact not only to the students, but to the teachers and librarians as well. With the librarian and teachers jointly planning and monitoring instruction, the needs of the students will be more effectively met.
This study sought to determine (1) the modes of support and planning given by the librarians to the teachers and vice versa; (2) the level of teacher-librarian collaboration of the institutions involved in the study; as well as (3) the similarities and differences of Level II PAASCU accredited schools in Quezon City with regard to teacher-librarian collaboration.
A total of six teachers and nine librarians, from Ateneo de Manila University Grade School, School of St. Anthony, and Siena College participated in the study. Two research instruments were used: (1) descriptive survey questionnaire and (2) the interview method. The results of the study revealed that: (1) teachers support librarians by making sure that their students utilize all the materials found in the library and the librarians on the other hand, make sure that these resources are readily made available to their users; (2) the current level of collaboration of the participating Level II PAASCU Accredited Schools can be categorized under Cooperation which means that these schools are practicing activities in the first level of collaboration; and (3) there are not so much difference in Level II PAASCU accredited schools in relation to teacher-librarian collaboration as they have the same concept of answers when it comes to the interview questions. However, the librarians of Ateneo de Manila University Grade School are more advanced compared to the other respondents as they have a closer relationship and a greater interaction to the teachers and students.
It is recommended that future researchers conduct the study during the time when the schools are not heavily preoccupied and to focus on Level III PAASCU Accredited Schools as it can provide different findings. Moreover, teachers and librarians should strengthen their collaboration as it can have good results in the students' achievement. Lastly, barriers to collaboration should be considered and appropriate actions should be done to achieve success in partnerships.
This study sought to determine (1) the modes of support and planning given by the librarians to the teachers and vice versa; (2) the level of teacher-librarian collaboration of the institutions involved in the study; as well as (3) the similarities and differences of Level II PAASCU accredited schools in Quezon City with regard to teacher-librarian collaboration.
A total of six teachers and nine librarians, from Ateneo de Manila University Grade School, School of St. Anthony, and Siena College participated in the study. Two research instruments were used: (1) descriptive survey questionnaire and (2) the interview method. The results of the study revealed that: (1) teachers support librarians by making sure that their students utilize all the materials found in the library and the librarians on the other hand, make sure that these resources are readily made available to their users; (2) the current level of collaboration of the participating Level II PAASCU Accredited Schools can be categorized under Cooperation which means that these schools are practicing activities in the first level of collaboration; and (3) there are not so much difference in Level II PAASCU accredited schools in relation to teacher-librarian collaboration as they have the same concept of answers when it comes to the interview questions. However, the librarians of Ateneo de Manila University Grade School are more advanced compared to the other respondents as they have a closer relationship and a greater interaction to the teachers and students. It is recommended that future researchers conduct the study during the time when the schools are not heavily preoccupied and to focus on Level III PAASCU Accredited Schools as it can provide different findings. Moreover, teachers and librarians should strengthen their collaboration as it can have good results in the students' achievement. Lastly, barriers to collaboration should be considered and appropriate actions should be done to achieve success in partnerships.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Teacher-Librarians -- Philippines -- Quezon City; Libraries and teachers -- Philippines -- Quezon City; Libraries -- Accreditation -- Philippines -- Quezon City